Quantifying high-speed running in rugby league: An insight into practitioner applications and perceptions - Bennett, T.; Marshall, P.; Barrett, S.; Malone, J. J.; Towlson, C. (International Journal of Sports Science & Coaching, 2023)
High-speed running has previously been documented as a popular metric among rugby league researchers. Researchers place importance on high-speed running due to its inclusion in assessing the demands of training and match-play to help prescribe accurate training loads and recovery methods. However, there is currently no information available as to how important rugby league practitioners perceive high-speed running to be and what methods are currently used by practitioners to quantify high-speed running. Furthermore, practitioners` perceptions of specific benefits, barriers and motivations when selecting high-speed running methods are also currently limited. Therefore, the aim of this study was to provide a current insight into the practice and perceptions of rugby league practitioners when quantifying high-speed running. This study surveyed practitioners working in the European Super League (n = 12) and the Australasian National Rugby League (n = 11). Ranking analysis established high-speed running to be the most important metric for both training practice and match-play. Absolute high-speed running thresholds were applied by 52% of respondents (n = 12) with the most common being 5.5 m·s-1 (n = 9). Individualised high-speed running thresholds were applied by 48% of respondents (n = 11) with the most common approach implementing peak sprint speed methods (n = 9). Absolute high-speed running thresholds are perceived to permit better group data comparison, whereas individualised methods are perceived to permit better interpretation of high-speed running data. Ultimately, practitioners are motivated to implement their chosen methods with the possibility of more accurately prescribed high-speed running thresholds, although the impracticality of specific testing procedures may act as a barrier.